2021
DOI: 10.14444/8061
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of Subaxial Cervical Spine Pedicles in a Middle Eastern Population

Abstract: Background: Pedicle screw instrumentation of the posterior cervical spine is the most secure form of fixation available to surgeons. It has not achieved widespread use yet in the Middle East, mostly due to concerns regarding its feasibility in the target population. A detailed morphometric analysis of the lower cervical spine pedicles using computerized tomography (CT) was proposed to address this issue.Methods: Two hundred and seventy patients were enrolled in the study. CT scans were reviewed by two experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Pedicular width, height and transverse angle measurements were made from three points in 300 adult patients. It was concluded that each patient should be considered individually for a safe surgical intervention (Alsaleh et al, 2021). For surgical interventions in the neck region to be successful, it is needed to know the detailed anatomical structure of the cervical vertebrae.…”
Section: Discussionmentioning
confidence: 99%
“…Pedicular width, height and transverse angle measurements were made from three points in 300 adult patients. It was concluded that each patient should be considered individually for a safe surgical intervention (Alsaleh et al, 2021). For surgical interventions in the neck region to be successful, it is needed to know the detailed anatomical structure of the cervical vertebrae.…”
Section: Discussionmentioning
confidence: 99%